IEEE INFOCOM 2007 - 26th IEEE International Conference on Computer Communications 2007
DOI: 10.1109/infcom.2007.266
|View full text |Cite
|
Sign up to set email alerts
|

Finding Self-Similarities in Opportunistic People Networks

Abstract: Abstract-Opportunistic network is a type of Delay Tolerant Networks (DTN) where network communication opportunities appear opportunistic. In this study, we investigate opportunistic network scenarios based on public network traces, and our contributions are the following: First, we identify the censorship issue in network traces that usually leads to strongly skewed distribution of the measurements. Based on this knowledge, we then apply the Kaplan-Meier Estimator to calculate the survivorship of network measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The experimental study by Chen et al (2007) is one of the first works, which seeks to find self-similarity in wireless AP association patterns. Although, it is well recognised that Internet traffic exhibit self-similarities (Garrett and Willinger, 1994;Leland et al, 1994;Paxson and Floyd, 1995;Crovella and Bestavros, 1997).…”
Section: Related Workmentioning
confidence: 99%
“…The experimental study by Chen et al (2007) is one of the first works, which seeks to find self-similarity in wireless AP association patterns. Although, it is well recognised that Internet traffic exhibit self-similarities (Garrett and Willinger, 1994;Leland et al, 1994;Paxson and Floyd, 1995;Crovella and Bestavros, 1997).…”
Section: Related Workmentioning
confidence: 99%
“…Similar to [10][21], we assume that two participating devices 7 In the Dartmouth network trace, there were 13,888 devices in the network, but only 5,148 of them had contact with other devices. 8 The inter-contact time distributions of the UCSD and Dartmouth traces have been shown to be heavy-tailed with the parameter α equal to 0.26 and 0.47 respectively, and both of them have also been proved to be self-similar [11]. in ad hoc mode encounter a communication opportunity (i.e., a network contact) if and only if they are both associated with the same AP during the same time period.…”
Section: A Evaluating Scenariosmentioning
confidence: 99%
“…Fig. 8 shows the CDF distribution of the web document quality received by a surfer, based on different coding and data forwarding schemes, at three time points in the UCSD scenario 11 . In Fig.…”
Section: Evaluation: Web Surfingmentioning
confidence: 99%
“…Since then it has been observed that the experimental inter-encounter time distributions appear to undergo a transition from power-law to exponential on a timescale of about one half day [20], and the reasons behind the observed exponentially distributed inter-encounter times in simulations using random walk mobility have been thoroughly examined [4]. Other analyses have involved the uncensoring of trace data [7], and node degree distribution.…”
Section: Related Prior Workmentioning
confidence: 99%